'Dear Comrade Chief Rep': Love, marriage and the family in the ANC in Exile in Tanzania. Issue 1 (2nd January 2017) - Lissoni, Arianna
ABSTRACT: Most studies about the South African liberation struggle have focused on political and strategic concerns at the level of formal organisations and their leadership. Yet the anti-apartheid struggle also impacted on personal relationships and the social life of those who put their lives in its service. This article draws on correspondence between members of the African National Congress in exile based in Tanzania and the organisation's chief representative in the region concerning permission, recognition and guidance on love, marriage and family-related matters in the period from the late 1970s to the early 1990s. It analyses how the demands of the struggle, and the difficult exile context, shaped love and family relationships and conceptions, and the ways in which individual cadres negotiated their personal lives while engaging in a political struggle as part of a collective movement. The disciplinary and parental role that the ANC in exile exercised through the bureaucratic process developed to manage these relations is also examined through the prism of the correspondence. The article argues that the governance of personal life by the ANC in exile was an integral part of nation-building and state-making – fulfilling both bureaucratic and affective functions.